Характеристика фракционного состава органического вещества торфов - Inisheva, L. I.; Szajdak, L. W.; Инишева, Л. И.; Шайдак, Л. (Издательство Тюменского государственного университета, 2013)
One of the perspective organic fertilizer resources is peat, containing many active components (humic acids, carbohydrates and others). A variety of the conditions of existence of bogs defines a significant variety of the chemical composition of peat forming peat deposits. The purpose ofthis article is to study the properties of the organic matter (OM) of peats in West Siberian taiga. Samples of representative peats (140) were selected on the territory of Tomsk Region and then an analysis of fractional group structure of the organic matter in peats was done. In these samples specific distribution of organic material fractions were revealed in various types and groups of peats. The reasearch shows that low-lying herbal and wood-herbal groups of peat can serve as optimal raw material base for production of organic fertilizers from peat. Одним из перспективных сырьевых источников для органических удобрений является торф. Многообразие условий существования болот определяет значительное разнообразие химического состава торфов, слагающих торфяные залежи. Цель исследования: изучить свойства органического вещества (ОВ) торфяных болот таежной зоны Западной Сибири. На территории Томской области было отобрано 140 образцов представительных видов торфов, в которых проведен анализ фракционно-группового состава органического вещества. Выявлены особенности распределения фракций органического вещества по видам и группам торфов разного генезиса. Показано, что в качестве оптимальной сырьевой базы для производства органических удобрений могут служить низинные травяная и древесно-травяная группы торфов.